Separate Treatment of Juvenile Offender in Malaysia and Bangladesh: An Overview - Ferdousi, Nahid (Journal of Malaysian and Comparative Law, 2014)
Delinquent children have the right to legal protection and fair treatment in a justice system that respects their human rights. Separate legislation along with child-friendly justice is very important in changing the life of offenders. The main objectives of the separate legal measures are protection, rehabilitation and reintegration to restore the delinquent children to normal living condition and to develop their personality as a law abiding and responsible citizen. But the law and policy for child protection is developed in different countries in conformity with the Convention on the Rights of the Child (CRC) 1989 and other international guidelines. The many differences and complexities of juvenile justice and the variations in practice have not been always easy to capture and reflect in these guidelines. Comprehensive juvenile justice systems do not exist in every country. This article assesses the legal mechanisms for protection of juvenile delinquents in Malaysia and Bangladesh.